2016
DOI: 10.1002/1873-3468.12070
|View full text |Cite
|
Sign up to set email alerts
|

A novel l‐arabinose‐responsive regulator discovered in the rice‐blast fungus Pyricularia oryzae (Magnaporthe oryzae)

Abstract: In this study we identified the l‐arabinose‐responsive regulator of Pyricularia oryzae that regulates l‐arabinose release and catabolism. Previously we identified the Zn2Cys6 transcription factor (TF), AraR, that has this role in the Trichocomaceae family (Eurotiales), but is absent in other fungi. Candidate Zn2Cys6 TF genes were selected according to their transcript profiles on l‐arabinose. Deletion mutants of these genes were screened for their growth phenotype on l‐arabinose. One mutant, named Δara1, was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…D and Supporting Information Table S2), LAD1 and FBP1 were down‐regulated (both 2.9‐fold) in Δ crf1 when cultured in L‐arabinose medium. PRD1 , LAD1 , LXR1 , XKI1 (Battaglia et al ., ), TKL1 (Fernandez et al ., ) and ARA 1 (Klaubauf et al ., ) were down‐regulated 3.6‐, 2.5‐, 2.8‐, 2.4‐, 3.4‐, and 3.3‐fold, respectively, in the appressoria of Δ crf1, based on qPCR analysis ( p < 0.05) (Fig. D).…”
Section: Resultsmentioning
confidence: 97%
“…D and Supporting Information Table S2), LAD1 and FBP1 were down‐regulated (both 2.9‐fold) in Δ crf1 when cultured in L‐arabinose medium. PRD1 , LAD1 , LXR1 , XKI1 (Battaglia et al ., ), TKL1 (Fernandez et al ., ) and ARA 1 (Klaubauf et al ., ) were down‐regulated 3.6‐, 2.5‐, 2.8‐, 2.4‐, 3.4‐, and 3.3‐fold, respectively, in the appressoria of Δ crf1, based on qPCR analysis ( p < 0.05) (Fig. D).…”
Section: Resultsmentioning
confidence: 97%
“…Despite having no significant sequence similarity to AraR, ARA1 appears to be the functional analog of AraR, controlling the arabinanolytic system as well as l -arabinose catabolism. A preliminary phylogenetic analysis shows that it is present only in the Sordariomycetes and Leotiomycetes (Additional file 2) and confirms that there is no significant sequence similarity to AraR [102]. This suggests that AraR and ARA1 are an example of parallel evolution in these fungal clades, which appears to be a relatively uncommon phenomenon for regulators in Ascomycetes.…”
Section: Transcription Factors Directly Involved In Plant Biomass Degmentioning
confidence: 87%
“…It is likely that another arabinanolytic transcription factor exists, that controls abf1 and abf3 [100, 101]. Recently, a new arabinose-responsive regulator was described in M. oryzae , that has orthologs only in Sordariomycetes and Leotiomycetes [102] (see “ l -Arabinose-responsive regulators (AraR and ARA1)”).…”
Section: Transcription Factors Directly Involved In Plant Biomass Degmentioning
confidence: 99%
“…While PDR-1 appears to combine functions of all three recently reported pectinolytic TFs: Ara1 (from M. oryzae ), GaaR (from B. cinerea ), and RhaR (from the Aspergilli ) [2931], it is likely not the sole TF involved in regulating pectin catabolism in N. crassa . At least three observations support this conclusion: (1) The Δ pdr - 1 strain has a major growth defect on pectin, but is still able to accumulate between 20 and 30% of WT biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, mostly in the highly pectinolytic fungi Aspergillus niger  ( A. niger ) and Botrytis cinerea ( B. cinerea ), have shown that individual sugars liberated from pectin by secreted enzymes, such as d -GalA, l -Ara, l -Rha and d -Gal, or their respective metabolic derivatives have an inducing potential for the corresponding gene products [2527]. Recently, transcription factors (TFs) that are conserved across fungi and that mediate the response to some of these monosaccharides have been identified: TRC1 and RhaR for l -Rha in Pichia stipitis ( P. stipitis ) and A. niger , respectively [28, 29], GaaR for d -GalA in B. cinerea [30] and Ara1 for l -Ara in Magnaporthe oryzae ( M. oryzae ) [31]. While identified in different fungi, these TFs have in common that they are responsible for regulating a subset of genes involved in the degradation of a particular pectin domain or pectic polysaccharide: HG for GaaR, the RG-I backbone for RhaR, and the arabinan side chains of RG-I (or hemicellulosic arabinan) for Ara1.…”
Section: Introductionmentioning
confidence: 99%